Early-Season Vegetable Insect Pests - Bauernfeind, Robert J. (My University, 1998)
This publication details several categories of insects that are associated with early-season vegetable production in Kansas.
MF1016_1998-03
Keywords: MF1016; Insects; Lawn and Garden; MF